Valuing cryptocurrencies: Three easy pieces - Michael C. Burda (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2021)
This paper surveys the capacity of simple macroeconomic models - 'three easy pieces' - to account for persistent and positive valuations of privately issued assets based on the blockchain. Each of these three models - transactions demand for a means of payment, consumption-based capital asset pricing, and search and matching - highlights important aspects of digital payments. The mutual interference of these jointly produced features may impede widespread use of cryptocurrencies until technological innovations have been developed to separate them.
Keywords: C00; 330; Virtuelle Währung; Makroökonomisches Modell; Theorie